Causation analysis and governance strategy for hazardous cargo accidents at ports: Case study of Tianjin Port's hazardous cargo explosion accident - Hua, Wenyu; Chen, Jihong; Qin, Quande; Wan, Zheng; Song, Lan (Marine pollution bulletin, 2021)
As an important part of the global shipping industry, hazardous cargo transportation at ports is concerned by countries around the world due to the great hazards and high risks during its operations. However, multiple hazardous cargo accidents have occurred at ports in recent years. The explosion accident of hazardous cargoes at Tianjin Port, China, in 2015 is a typical case. It is a topic worth in-depth study to figure out how to analyze the causation factors of such accident and propose effective governance strategies against them. This article takes the hazardous cargo explosion at Tianjin Port of China as the subject and systematically analyzes the causation factors of the accident based on the Fault Tree Analysis (FTA) method. It proposes a strategy for governing hazardous cargoes at the port. The analysis results show that the hazardous cargo explosion at the port has complicated causation factors, among which management and human factors play a predominant role in the overall accident causation structure. Other factors include environmental factors and cargo & facility factors. Finally, the corresponding safety governance strategy is proposed based on the structural relationship of various accident causation factors in the above analysis. This study can offer guidance for port enterprises to reduce hazardous cargo accidents at ports and provide an important basis for port authorities to formulate strategies on emergency management and emergency decision-making of hazardous cargo accidents at ports. •Hazardous cargo operation accidents affect green port development.•Use the Fault Tree Analysis method to explore related causation factors•Case study of Tianjin Port's hazardous cargo explosion accident•Example research provides decision-making basis for the management of green ports.